PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PENDEKATAN SAINTIFIK MODEL GUIDED DISCOVERY DAN EFEKTIVITASNYA TERHADAP PENGUASAAN KONSEP BIOLOGI SISWA SMA NEGERI 1 BAYAN - Raden Sumiadi; Dwi Soelistya Dyah Jekti; Jamaluddin - (Postgraduate, University of Mataram, 2016)
The purposes of this research are 1) developing learning device based on scientific approach with model of guided discovery 2) knowing elegibility peripheral of study base on scientific approach model of guided discovery 3) Knowing effectiveness peripheral of study to ability domination biological concept. Development peripheral of study use model 4D from Tiagrajan S. Semmel & modified Semmel become three phase, that is phase of define, design, and development. Result of development peripheral study is hereinafter analysed to use formula of presentase adapted for mean the tables criterion result of validasi. To know effectiveness peripheral of study to domination biological concept, peripheral of study in aplicate limited group in SMAN 1 Bayan and analysed to use formula of presentase complete individual. Result of research show, peripheral of study base on scientific approach model of guided discovery categorized good (valid) and very good (very valid) competent so that used in course study of biology in SMAN 1 Bayan, and peripheral study can streamline ability of domination biological concept student.Keyword: Learning device, Scientific approach, Guided discovery, Mastery of biological concept